Profesionalisme Guru dalam Penggunaan Media Audiovisual pada Pembelajaran Fikih di Kelas IV MIN 44 Bireuen - Wahyuni, Sri (Pase: Journal of Contemporary Islamic Education, 2022)
This study aims to explain teacher professionalism in the use of audiovisual media in learning Fikih, and explain the constraints and efforts in using audiovisual media in learning Fikih at grade IV MIN 44 Bireuen. In this qualitative research, all data was collected through interviews, observation, and document study. Furthermore, data analysis was carried out through the stages of data reduction, data display, and data verification. The results showed that teacher professionalism in using audiovisual media in learning Fikih at grade IV MIN 44 Bireuen was shown by the teacher's ability to use audiovisual media, the ability to display learning videos related to everyday life. The obstacles faced by teachers in using audiovisual media in learning Fikih at grade IV MIN 44 Bireuen: (1) the limited LCD projector as a learning tool which requires a rotating schedule for its use, (2) the lack of time allotted for Fikih lesson. Efforts made by Fiqh teachers to overcome obstacles in the use of audiovisual media in learning Fikih at grade IV MIN 44 Bireuen by making rules and schedules for using the LCD projector with the permission of the Head of Madrasah and socializing it to the board of teachers regarding the learning schedule.